The sanrafaelic remagnetization of precordillera in the permian: New evidence - Rapalini, A.E. (2005)
A paleomagnetic study, carried out on 9 sites of the La Flecha Formation (facies Los Sapitos, Upper Cambrian, Marjuman-Steptoean) exposed along the la Angostura creek, Precordillera of La Rioja (29.5°S, 68.7°W), permitted to determine two magnetic components. One is postectonic and of low coercivities and unblocking temperatures (A, Dec: 7.5°, Inc: -40.3°, a95: 10.1°, N: 6), being interpreted as a recent remanence of probable viscous origin. A second, pretectonic, component was isolated in seven sites with opposite polarities and is likely carried by magnetite (B, Dec: 206.9°, Inc: 63.3°, a95: 12.8°, N: 7). The paleomagnetic pole position for this component (Lat: 63.8°S, Long: 244.6°E, dp: 15.9°, dm: 20.2°) suggests that the remanence was acquired by the end of the Permian and it is interpreted as produced by the regional remagnetization associated with the San Rafael orogenic phase found in other units of the Precordillera. An analysis of pole positions, type of magnetizations, polarities and geographic distribution of the remagnetized units suggests a pattern of time-space migration of the remagnetization from west to east, between the Early Permian and the Permian-Triassic. This pattern is consistent with a model of remagnetization by migration of fluids expelled from the orogenic area that reached rocks not involved directly in the deformation. The pole position obtained for La Flecha Formation also suggests the lack of major tectonic rotations in the study area since the Permian. © 2005 Asociación Geológica Argentina.